Bioenergy estimation of spring barley and oat varieties’ cultivation depending on seed-sowing rates in the Krasnoyarsk forest-steppe - L. K. Butkovskaya; V. Е. Mudrova; А. О. Polyakov (Зерновое хозяйство России)
The purpose of the current study was a bioenergy estimation of different seed sowing rates of spring barley and oat varieties in the conditions of the Krasnoyarsk forest-steppe. The trials were carried out in the village of Minino, Emelyanovsky district, Krasnoyarsky Krai in 2021–2023. The objects of the study were the spring barley varieties ‘Abalak’, ‘Takmak’, ‘Oplot’, ‘Biom’ and the spring oat varieties ‘Tubinsky’, ‘Sayan’, ‘Kazyr’, ‘Uspekh’. Experimental schemes were as follows: barley varieties with seeding rates of 3.5, 4.0, 4.5 million germ. grains per hectare; oat varieties with seeding rates of 4.0, 4.5, 5.0 million germ. grains per hectare. High yields (5.60–5.71 t/ha) were produced by the barley varieties ‘Oplot’ and ‘Takmak’, while other varieties produced less on 0.9–1.4 t/ha. There has been revealed that the reproduction coefficient of barley seeds increased to 34.6 at a seed-sowing rate of 3.5 million germ. grains per hectare and decreased to 22.2–31.3 at a seed-sowing rate of 4.5 million germ. grains per hectare. There has been established that among oats, the variety ‘Tubinsky’ produced the highest yield of 4.79 t/ha at a seeding rate of 5.0 million germ. grains per hectare, followed by the variety ‘Sayan’ with 4.85 t/ha, the new promising variety ‘Uspekh’ with 4.67 t/ha and ‘Kazyr’ with 4.53 t/ha. The reproduction coefficient reached 26.9–29.7 with 4.0 million germ. grains per hectare and 21.3–23.5 at 5.0 million germ. grains per hectare. The energy estimation has shown that the optimal seed-sowing rate is 4.5 million germ. grains per hectare for barley varieties and 4.0 million germ. grains per hectare for oat varieties. The total energy increase (the difference between the total energy and energy costs) was 94.4 and 83.2 GJ/ha for the barley varieties ‘Takmak’ and ‘Oplot’, respectively and 58.9 and 59.0 GJ/ha for the oat varieties ‘Tubinsky’ and ‘Sayan’.